Effects of exercise on bone mineral density and bone turnover markers in adults: a systematic review and meta-analysis - Miao, Tingting; Li, Xun; Zhang, Wenhua; Liu, Jie; Xiao, Yi; Wang, Xiaoqiang (Frontiers in Physiology, 2026)
BackgroundThe incidence of osteoporosis and associated fracture risk increases significantly with age, making it a major global public health concern.ObjectiveThis study aims to evaluate the impact of exercise on bone mineral density (BMD) at the lumbar spine, femoral neck, and total body in adult women across different age groups, and to further assess the efficacy of different exercise modalities on BMD at these sites. A parallel objective is to investigate the effects of exercise on key bone turnover markers, including the bone formation markers osteocalcin (OC), bone-specific alkaline phosphatase (BALP), and procollagen type I N-terminal propeptide (P1NP), as well as the bone resorption markers C-terminal telopeptide of type I collagen (CTX) and tartrate-resistant acid phosphatase 5b (TRACP-5b). The ultimate goal is to provide evidence for optimizing exercise strategies to enhance bone mass and prevent osteoporosis.MethodsA systematic search was conducted in PubMed, Embase, the Cochrane Library, and Web of Science from inception to 14 November 2025. Randomized controlled trials (RCTs) were screened according to predefined inclusion and exclusion criteria. Relevant data were extracted, and study quality was assessed using the cochrane risk of bias tool (ROB2). Meta-analyses were performed using Stata 17. Publication bias was evaluated using Egger’s test, and sensitivity analyses were conducted to assess the robustness of the findings.ResultsA total of 22 RCTs involving 1,051 participants were included. The meta-analysis showed that, in subgroup analyses by age, exercise significantly increased lumbar spine BMD [SMD = 0.46, 95% CI (0.16, 0.76), P < 0.01] and femoral neck BMD [SMD = 0.42, 95% CI (0.13, 0.71), P < 0.01] in young adult women under 30 years of age. Subgroup analysis by exercise modality indicated that combined exercise significantly improved femoral neck BMD [SMD = 0.49, 95% CI (0.08, 0.90), P = 0.02] and total body BMD [SMD = 0.52, 95% CI (0.08, 0.97), P = 0.02]. Furthermore, exercise significantly elevated levels of bone formation markers, including OC [SMD = 0.41, 95% CI (0.17, 0.64), P < 0.01] and BALP [SMD = 0.71, 95% CI (0.36, 1.06), P < 0.01]. Subgroup analysis by exercise session duration showed that exercise programs shorter than 4 months were associated with increased OC [SMD = 0.41, 95% CI (0.12, 0.71), P < 0.01] and P1NP [SMD = 0.69, 95% CI (0.14, 1.24), P = 0.01], while BALP levels were significantly elevated both in interventions shorter than 4 months [SMD = 0.56, 95% CI (0.10, 1.01), P < 0.01] and those longer than 4 months [SMD = 0.94,95% CI (0.39, 1.48), P = 0.02].ConclusionThis systematic review and meta-analysis indicate that exercise significantly increases lumbar spine and femoral neck BMD in young adult women under the age of 30. Additionally, combined exercise shows significant benefits in improving femoral neck and whole-body BMD in adult women. Furthermore, in terms of bone metabolism, exercise effectively promotes the elevation of bone formation markers OC and BALP in adults. Specifically, short-term interventions (less than 4 months) significantly increase OC and P1NP levels, while BALP levels show significant increases following both short-term and long-term (≥4 months) interventions.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251001516.